Factors impacting on childhood nutrition: The experience of mothers in a rural Ghanaian community. (1st December 2021) - Kukeba, Margaret Wekem; Callery, Peter; Fallon, Debbie
Abstract: Despite globally recommended infant and young child feeding (IYCF) practices, inadequate Child feeding remains a global challenge and the root cause of undernutrition. Most mothers who primarily feed children in most developing settings appear to have received information on the IYCF practices. We explored mothers' limitations to provide children optimally in a rural Ghanaian community. We interviewed 42 family members, including parents and grandparents of thirty-two children under five years, from fifteen households using an ethnographic fieldwork approach. We observed and participated in food preparation and child feeding and interviewed religious leader, diviners. Households' decision-making arrangements, mothers, emerging roles and inconsistency of fathers' roles, competing sources of knowledge poverty, food insecurity and the nature of the community's social interactions and policing of women's child feeding practices are issues mothers have to navigate to feed children in the study community. Cultural custodians should be given child nutrition and providing information. Mothers should be empowered to manage child feeding and emerging roles.